The effects of season on fat and fatty acids contents of shrimp and prawn species. Issue 3 (29th January 2013) - Ayas, Deniz; Ozogul, Yesim; Yazgan, Hatice
Abstract The effects of seasons on the lipid content and fatty acid compositions of five different shrimp and prawn species (green tiger prawn – Penaeus semisulcatus, kuruma prawn – Marsupenaeus japonicus, caramote prawn – Melicertus kerathurus, deepwater pink shrimp – Parapenaeus longirostris, speckled shrimp – Metapenaeus monoceros) were evaluated. Results showed that lipid content ranged from 0.89 to 1.55% in muscle, showing that all species were considered as lean. There were significant differences (p<0.05) in the levels of saturated fatty acids (SFA), monounsaturated fatty acids and polyunsaturated fatty acids (PUFA) in terms of season and species. They were rich in n‐3 fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The highest proportions of EPA were obtained from kuruma prawn (180.9 mg/100 g) in spring and deepwater pink shrimp (173.2 mg/100 g) and caramote prawn (146.3 mg/100 g) in summer. Kuruma prawn had the highest DHA in spring (140.8 mg/100 g) followed by deepwater pink shrimp (132.2 mg/100 g) and caramote prawn (129.6 mg/100 g) in summer. The results also showed that the seasons affected lipid content and the fatty acid composition of shrimp and prawn species. Practical Application: The beneficial effect of seafood consumption on human health has been related to the high content of n‐3 fatty acids, especially EPA (20:5n‐3) and DHA (22:6n‐3). The ratios of n‐6/n‐3, PUFA/SFA and EPA + DHA are considered as useful criteria for comparing relative nutritional and oxidation values of marine oils. In the current study, the influence of seasonality on the lipid content and the fatty acid compositions of shrimp and prawn were investigated in order to find the best source of n‐3 fatty acids during the year.